Deciphering the nexus of trade frictions, pollution, and export quality - Tongsheng Xu; Xin Yu; Liang Ding; Yating Zhang (Humanities & Social Sciences Communications)
Abstract In this study, we explore the intricate relationship between domestic trade costs, pollution emissions, and the quality of exports. Utilizing a decade of provincial data from China, we employ spatial econometric models to dissect the nexus among these factors. Our analysis reveals a significant spatial dependency linking export quality with environmental pollution, indicating that increases in inter-regional trade costs not only degrade export quality within a region but also influence neighboring provinces. Pollution emissions emerge as a critical mediator in this relationship. Specifically, we find that interprovincial trade frictions suppress export quality through both direct cost channels and indirect environmental effects, with heterogeneous impacts across enterprise ownership types. These results underscore the significant impact of reducing domestic trade costs on enhancing economic efficiency, minimizing environmental pollution, and improving the quality of exports. By integrating trade cost, environmental burden, and export quality into a unified spatial framework, this study offers novel empirical evidence and contributes methodologically by applying the Spatial Durbin Model to quantify spatial spillover and mediation effects. The findings not only illuminate the interconnected nature of trade dynamics and environmental considerations but also provide compelling evidence that strategic policy interventions in trade can lead to sustainable development. This study contributes to the fields of trade economics and environmental policy, highlighting actionable insights that policymakers can leverage to foster economic growth while protecting the environment.